Social Entrepreneurship: Driving Change and Creating Positive Societal Impact - Khan, Mohammed Abdul Imran; Jamil, Syed Ahsan; Azharuddin, Syed (Current Topics on Business, Economics and Finance Vol. 6, 2023)
Social entrepreneurship has gained significant attention in recent years as a means of addressing pressing social and environmental challenges. This chapter explores the relationship between innovative business models and their impact on society. Drawing on a comprehensive review of literature, the chapter provides evidence that social entrepreneurship can drive change through innovative business models that have a positive impact on society. The chapter also identifies key factors that contribute to the success of social entrepreneurship, including collaboration, networking, and a commitment to social and environmental values. Social entrepreneurship is a rapidly growing field that seeks to create innovative and sustainable solutions to social problems. As society continues to face new challenges, social entrepreneurs are uniquely positioned to address these issues and create positive change. Social entrepreneurship has gained momentum over the last decade, as entrepreneurs have begun to recognize that profit and social impact are not mutually exclusive. However, social entrepreneurship is a relatively new field, and its future is uncertain. This chapter provides an overview of the current trends, challenges, and opportunities facing social entrepreneurship, based on a review of recent literature. Most research findings suggest that social entrepreneurship will continue to grow, as more entrepreneurs recognize the benefits of social impact. However, there are also significant challenges, including funding, scalability, and regulatory hurdles. To overcome these challenges, social entrepreneurs will need to be creative, collaborative, and resilient, and will need to leverage new technologies and business models.